Estudo fitoquímico do tronco e raiz de Maytenus salicifolia Reissek (Celastraceae) e avaliação da atividade biológica de seus constituintes e de ésteres derivados do lupeol - Cassia Gincalves Magalh?es (2012)
In this work it is described the phytochemistry study of stems and roots of Maytenus salicifolia Reissek (collected in Ouro Branco city, Minas Gerais state), which chemical constitution and biological activity have not been yet reported in the literature. It were isolated eight known compounds from the stems:dioxofriedelane, lupeol, betulin, friedelin, 30-hydroxyfriedelan-3-one, 3-oxo-15alpha,28-di-hydroxy-lup-20(29)-ene, lup-20(29)en-3,30-diol, and 28-hydroxylup-20(29)-en-3-one. Siringaldehyde, 3'-methoxy-4'-hydroxy-trans-cinamaldehyde, pinostrobin, 4'-O-methylepigallocatechin, proanthocyanidin A, beta-sitosterol, ferruginol, 6,7-dehydroferruginol, glutinol, 29-hydroxy-friedelin, friedelan-1,3-dione, glochidonol, 3-epiglochidiol, lupenone, 30-hydroxy-lup-20(29)-en-3-one, 11alpha-hydroxyglochidone, glochidone, rigidenol, nepeticin, abruslactone A, tingenone and pristimerin were isolated from roots.. It was also isolated a triterpenes mixture, identified as 3-oxo-olean-9(11):12-diene / 3-oxo-ursan-9(11):12-diene and a dimmers mixture, identified as 7,8-dihydroisoxuxuarin Aalpha / isoxuxuarin alpha. Three compounds are new in the literature: 2'-(2-hydoxypropil-4'-O-methylepigallocatechin), 16beta-hydroxypristimerin e salicassin, obtained from root extracts. The last one is the first adduct reported composed of a chalcone and a diterpene. Eleven esters were also synthesized from lupeol isolated of this specie, six aliphatic and five aromatic esters. The compounds and extracts isolated from M. salicifolia, as well as lupeol esters were submitted to several biologic assays. The hexanic, ethyl acetate and ethanolic extracts from roots were evaluated against oral cavity microorganisms. All the extracts evaluated were active against at least one of microorganisms, and Candida albicans was sensible at all extracts assayed. Rigidenol exibited inhibitory activity against Helicobacter pylori, as well as 16- hydroxypristimerin, which also presented cytotoxic activity against HeLa and A-549 cell lines. Lupeol palmitate was cytotoxic for K-562 cell line. Lupeol caproate inhibited the H. pylori growth, as well as the activity of acethylcholinesterase enzyme. This enzyme was also inhibited by 30-hydroxyfriedelan-3-one. The results obtained contributed for the chemotaxonomic study of Celastraceae family and show that M. salicifolia can be an alternative source of compounds that are possible prototypes of drugs that acts in different diseases.